Foreign direct investment in transition economies: An option approach to sovereign risk - Michele Moretto; Paola Valbonesi (Fondazione Eni Enrico Mattei (FEEM), 1997)
At the start of the transition process in previously centrally planned economies the inflow of foreign capital was considered one of the main factors that allows the reduction of the economic and social costs of transformation. However, in practice, the role of foreign capital has appeared to be less significant than expected. Relying on the relationship between irreversible investment and the option pricing approach, we show that the link between sovereign risk and investment flexibility provides an explanation of capital inflow slow-downs and that such an explanation depends crucially on the expected persistence of policies affecting capital mobility.
Keywords: F21; P21; 330; Transition economics; Capital mobility; Investment irreversibility; Direktinvestition; Länderrisiko; Optionspreistheorie; Übergangswirtschaft; Theorie; Osteuropa